IMPLEMENTASI KEBIJAKAN BRIGADE SIAGA BENCANA DALAM TANGGAP DARURAT DI KABUPATEN BANTAENG - M. Munawwir; Alyas, M.S; Lukman Hakim (Program Magister Ilmu Administrasi Publik, Universitas Muhammadiyah Makassar, 2021)
Disaster in Emergency Response in Bantaeng Regency with several factors affecting the implementation of policies, standards and policy objectives resources, characteristics of the implementing agencies, attitude and tendency of implementers (Disposition) , clarity of information on communication between organizations and implementing activities (inter-organizational communication and enforcement activities) and conditions of the economic, social and political environment (economic, social and political conditions). The method used in this research was descriptive qualitative using observation, interview, and documentation instruments. Then data analysis techniques through data reduction, data presentation, and drawing conclusions. The results showed that; (1) Standard and policy objectives (standards and objectivity), the legal basis for its implementation is by the 1945 Constitution article 28 verse 1, which was then technically translated through the Decree of the Minister of Health of the Republic of Indonesia Number 462 of 2002 concerning Safe Community. This government policy is expected to be able to enhance public health status. (2) Resources, in terms of the number and expertise of the human resources assigned to the BSB team, are sufficient. (3) The characteristics of the implementing agencies, District government support for this program is quite adequate both in terms of budget and needs. (4) The attitude and tendency of the implementers (Disposition), the understanding of policy implementers about the standards and objectives of this policy is well understood (5) Clarity of information communication between organizations and activities implementer (inter-organizational communication and enforcement activities) that in order to provide clarity of the information to the public, BSB officers involve community groups as information support media (6) Economic, social and political conditions. Strong support for the success of the Disaster Preparedness Brigade program lies in the social capital owned by The Regent of Bantaeng, Nurdin Abdullah as the initiator.